Cutting Parameter Optimization based on Online Temperature Measurements - Kara Ali, Abdelillah Djamal; Benhadji Serradj, Nasreddine; Ghernaout, Mohamed El Amine (Engineering, Technology & Applied Science Research, 2023)
The deformation of metallic materials during the machining operation requires a significant amount of energy. During the chip formation process and due to the plastic deformation of the metal and the friction along the tool-part interface, the thermal loads generated are strongly impacted by the cutting factors. Thus, the choice of optimized cutting conditions is essential to control the quality of the work required. The aim of the present experimental study is to optimize the cutting parameters using temperature measurements. The average temperature of the cutting tool is studied using a FLIR A325sc type infrared camera. Optimal cutting parameters for each performance metric were obtained using the Taguchi techniques.